2014
DOI: 10.1016/j.foodchem.2013.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin–β-cyclodextrin inclusion complex: Stability, solubility, characterisation by FT-IR, FT-Raman, X-ray diffraction and photoacoustic spectroscopy, and food application

Abstract: Curcumin was complexed with β-CD using co-precipitation, freeze-drying and solvent evaporation methods. Co-precipitation enabled complex formation, as indicated by the FT-IR and FT-Raman techniques via the shifts in the peaks that were assigned to the aromatic rings of curcumin. In addition, photoacoustic spectroscopy and X-ray diffraction, with the disappearance of the band related to aromatic rings, by Gaussian fitting, and modifications in the spectral lines, respectively, also suggested complex formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
193
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 449 publications
(212 citation statements)
references
References 27 publications
14
193
0
5
Order By: Relevance
“…Cur spectrum (Figure 6) indicated that it existed in the keto-enol tautomeric form because bands in the most significant carbonyl region from 1800 to 1650 cm -1 were detected [56]. Cur exhibited several peaks, one at 806 cm -1 due to γ(CH) of aromatic and skeletal CCH [57], a band of peaks was observed in region (1000-1300 cm -1 ) which can be attributed to the symmetric and asymmetric configurations of C-O-C chains, peak at 1436 cm -1 was attributed to CH2 bending, while peak at 1502 cm -1 due to C=O and C=C vibration, peak at 1626 cm -1 C=O stretching, peak at 2840 cm -1 was assigned to C-H stretching of methyl group, peak at 3014 cm -1 was due to C-H stretching of aromatic ring, and peak at 3507 cm -1 was attributed to free -OH group vibration [36].…”
Section: Drug Loading and Characterization N 2 Adsorption/desorption mentioning
confidence: 99%
“…Cur spectrum (Figure 6) indicated that it existed in the keto-enol tautomeric form because bands in the most significant carbonyl region from 1800 to 1650 cm -1 were detected [56]. Cur exhibited several peaks, one at 806 cm -1 due to γ(CH) of aromatic and skeletal CCH [57], a band of peaks was observed in region (1000-1300 cm -1 ) which can be attributed to the symmetric and asymmetric configurations of C-O-C chains, peak at 1436 cm -1 was attributed to CH2 bending, while peak at 1502 cm -1 due to C=O and C=C vibration, peak at 1626 cm -1 C=O stretching, peak at 2840 cm -1 was assigned to C-H stretching of methyl group, peak at 3014 cm -1 was due to C-H stretching of aromatic ring, and peak at 3507 cm -1 was attributed to free -OH group vibration [36].…”
Section: Drug Loading and Characterization N 2 Adsorption/desorption mentioning
confidence: 99%
“…2. In FT-IR analysis curcumin shows characteristic bands at 3509 cm −1 (phenolic OH stretch), 1508, 1280, 1029, 1592 cm −1 etc (Mangolim et al 2014). Chitosan shows broad peak at 3655 cm −1 which corresponds to its amine group, and peak at 1626 cm −1 which corresponds to its amide group (Brugnerotto et al 2001).…”
Section: Fourier Transform Infra Red Spectroscopy (Ft-ir) Analysismentioning
confidence: 99%
“…Conversely, several marketed polyherbal formulations are available without labeled claim on relative percentage composition of individual curcuminoids. 12 Several methods were reported for the estimation of curcumin in different pharmaceutical and herbal formulations by using UV, 13 HPLC, 14 UPLC, 15 HPTLC, 16 FT-IR 17 and others hyphenated methods. 18,19 However, these techniques are not suitable for analyzing compounds in combinations of polyherbal formulations like Ayurvedic or Chinese medicinal products, since they contain more than one herb.…”
Section: Introductionmentioning
confidence: 99%